Pengaruh Pelatihan Kerja, Kompensasi Finansial Serta Disiplin Kerja Pada Kinerja Pegawai Di PT. Bayu Jaya Kusuma Bali - Anak Agung Ngurah Restu Gautama; A.A.N Oka Suryadinatha Gorda; I Made Mai Noval; Rai Puspa Sugianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research is to gather information related to the contribution of job training, financial compensation, and work discipline to employee performance at PT. Bayu Jaya Kusuma Bali. The sample in this study were 54 samples. The analysis technique in this study used multiple linear regression analysis, classical assumption test, t test, f test and determination analysis. This study obtained the results of H1 obtaining a t value of 4,670 with a p-value of 0.000 <alpha = 0.05, which identified a significant positive effect related to job training variables on employee performance.. H2 obtained a t value of 4,404 and a p-value of 0.000 <alpha = 0.05, which indicates that there is a significant positive effect of financial compensation on employee performance. H3 has a t-value of 3,197 and a p-value of 0.002 <alpha = 0.05, which indicates a positive and significant effect of the work discipline variable on employee performance. H4 has an F value of 70,708 and a p-value of 0.000 <alpha = 0.05, which identifies a positive and significant effect between job training, work compensation, work discipline on employee performance. Keywords: Job Training, Financial Compensation, Work Discipline, Employee Performance